The Application of Ilahiyah Accounting in Fostering the Character of Muslim Students: A Case Study at the Accounting Department of Pontianak State Polytechnic - Baidhillah Riyadhi; Nelly Mujahidah; Reno Piansyah; Zulfikar; Robby Mauludy Arif (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2025)
This study explores the application of Ilahiyah accounting in shaping the character of Muslim students majoring in Accounting at Pontianak State Polytechnic. The central issue addressed is the limited understanding among some students who perceive profit solely in material terms, thereby overlooking the immaterial dimensions emphasized in Islamic teachings. Employing a descriptive qualitative approach, this research adopts the Bayani method an analytical framework grounded in critical interpretation of relevant Qur’anic verses and Prophetic Hadiths. The findings reveal that integrating divine accounting principles based on the Qur’an and As-Sunnah effectively cultivates student character development that transcends mere financial orientation. Instead, it fosters an awareness of moral, ethical, and spiritual responsibilities. This study contributes to reinforcing an Islamic-values-based accounting paradigm, aiming to produce Muslim accountants endowed with integrity and holistic accountability.